Organizational commitment, patient satisfaction and loyalty in the first-level health facilities - Febri Endra Budi Setyawan; Stefanus Supriyanto; Ernawaty Ernawaty; Retno Lestari (International Journal of Public Health Science (IJPHS), 2022)
Patient satisfaction and loyalty are widely cited as markers of healthcare quality. Organizational commitment assists first-level health facilities in achieving the goals by incorporating physicians in the implementation of holistic and comprehensive care. This study aims to analyze a structural model of physician organizational commitment, patient satisfaction, and loyalty in first-level health facilities. This study used an explanatory research design with a total sample of 199 physicians and 980 patients in 30 public and private first-level health facilities within the collaboration of national healthcare and social security, chosen by systematic random sampling. Analysis was performed by using partial least squares–structural equation modeling (PLS-SEM). Physician factors, organizational factors, and non-organizational factors have the strongest influence on physician organizational commitment (80.2%). To sum up, major efforts should be made to improve organizational commitment among physicians in providing holistic and comprehensive care in first-level health facilities to boost patient satisfaction and loyalty.